Phantoms of Remembrance Memory and Oblivion at the End of the First Millennium - Geary, Patrick J. (Princeton (N.J.), Chichester : Princeton University Press, 1994)
TLS, 16/06/95, p. 25 (Murray, A.)
Notes, bibliogr., index